PENGARUH PAJAK HOTEL, PAJAK PENERANGAN JALAN, PAJAK REKLAME, DAN RETRIBUSI PELAYANAN PERSAMPAHAN/KEBERSIHAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BANTUL - Teguh Erawati; Miftah Hurohman (Universitas Sarjanawiyata Tamansiswa, 2017)
This research is to find out how big the Effect of Taxes, street lighting tax, advertisement tax and Service Fees Waste / Cleanliness against region income Bantul either partially or simultaneously in the Office of Revenue, Finance and Asset Management Area (DPPKAD) Bantul. Statistical method uses multiple linear regression analysis including test F and test t were processed using SPSS version 17.0.Research results show that the hotel tax, street lighting tax, advertisement tax, and levies Waste Services / Hygiene affect the original income. Simultaneous research results show that the hotel tax, street lighting tax, advertisement tax, and levies Waste Services / Cleanliness have significantly positive effects on the original income together. Independent Variables and Dependent Variables affect 31.4%, while 68.6% are influenced by other factors which are not described in regression model.Â Keywords: Hotel tax, street lighting tax, advertisement tax, and levies Waste Services / Hygiene, First income of Regions.